SiFEUP - Lígia M. Ribeiro (2001)
The information system of the Faculdade de Engenharia da Universidade do Porto is an integrated administrative IS, covering aspects ranging from the school infrastructures and the academic records, to the course plans, scientific productivity or the external assessment processes. It has been built in-house, since 1996, and it has enabled the progressive modernization of many processes and services providing more accurate decision support. This report presents the main aspects of the system organized according to the rules for submission to the EUNIS Elite Award.